Vibration control mechanism of the metabarrier under train load via numerical simulation. (October 2019) - Zhao, Caiyou; Wang, Liuchong; Liu, Dongya; Gao, Xing; Sheng, Xi; Ping, Wang
The problem of ambient vibration caused by rail transit continues to grow, and control effect requirements of different vibration reduction measures are always increasing. A new kind of vibration isolator used for floating slab tracks (FST) has been developed, called a metabarrier. Based on the bandgap properties of phononic crystals, it can realize a better vibration reduction capacity in certain frequency ranges with the same vertical stiffness as the original device. In order to study the vibration reduction characteristics of metabarriers under actual train loading action, two vibration isolators—a steel-spring vibration isolator and a metabarrier—were used to establish a train–FST–substrate dynamic coupling model. This study shows that the reduction capacity influenced by the phononic crystal bandgap is stable under different train speeds. In addition, under train load, the metabarrier can be used not only to isolate vibration by means of the bandgap, but also to absorb vibration dynamically, further expanding the vibration reduction frequency range. With optimized frequency range, metabarriers can reduce the acceleration vibration level by more than 9 dB over steel-spring vibration isolators.